Allicin as a possible adjunctive therapeutic drug for stage II oral submucous fibrosis: a preliminary clinical trial in a Chinese cohort. Issue 12 (December 2015) - Jiang, X.; Zhang, Y.; Li, F.; Zhu, Y.; Chen, Y.; Yang, S.; Sun, G.
Abstract: The objective of this study was to investigate the efficacy and safety of allicin in the treatment of stage II oral submucous fibrosis (OSF) in a Chinese patient cohort. A randomized clinical trial was performed. Triamcinolone acetonide (TA) or allicin was injected intralesionally weekly for 16 weeks. Improvements in mouth opening, burning sensation, and oral health-related quality of life were evaluated. Forty-eight subjects completed the study without obvious adverse reactions. At 40 weeks, the net gain in mouth opening was 2.27 ± 0.84 mm in the TA group and 5.16 ± 1.04 mm in the allicin group. Burning sensation improved by 2.79 ± 0.87 in the TA group and by 4.33 ± 1.04 in the allicin group. The OHIP-14 score improved by 4.67 ± 2.94 in the TA group and by 12.58 ± 9.82 in the allicin group. Allicin intralesional injections improved mouth opening, burning sensation, and oral health-related quality of life in these stage II OSF patients. Allicin appears to be a potential adjunctive therapeutic drug.